Pengembangan Media Articulate Storyline 3 untuk Meningkatkan Literasi Digital Siswa Madrasah Ibtidaiyah - AGUS AHMAD DURRI (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Advances in information technology have driven the integration of interactive digital media into learning. This narrative review aims to synthesize research findings on the use of Articulate Storyline 3 at the elementary school/MI level, as well as its implications for students’ digital literacy. A literature search was conducted through Google Scholar, Garuda Portal, SINTA, DOAJ, ResearchGate, and the PTKIN e‑journal platform, using keywords related to interactive learning media, Storyline 3, mathematics for SD/MI, and digital literacy. Eight articles met the inclusion criteria, covering topics such as plane figures, solid shapes, fractions, sets, mathematical communication, and numeracy literacy. The review results show that Storyline 3‑based media improves students’ understanding of mathematical concepts, creative thinking abilities, learning motivation, and digital literacy through interactive features such as animations, quizzes, drag‑and‑drop activities, and simulations. Limitations of the reviewed studies include their scope limited to SD/MI institutions, exclusive focus on Storyline 3, small sample sizes, and the lack of long‑term evaluation of digital literacy development. In conclusion, Articulate Storyline 3 is effective in enhancing mathematics learning and digital literacy at MI, with potential for further development to suit broader educational contexts.